High-performance capillary electrophoresis : theory, techniques, and applications - Khaledi, Morteza Gholi (John Wiley, 1998)
A complete and up-to-date manual on HPCE theory and practiceHigh Performance Capillary Electrophoresis brings together in one volume essential coverage of the theory, techniques, and applications of this highly useful and efficient technology.Suitable for the novice as well as the experienced user of HPCE, this book features expert contributions from highly respected scientists representing a wide range of disciplines. Chapters, which are grouped into sections to make information easy to find, cover:* Theory and principles of the six HPCE techniques* Detection systems, including indirect detection* Essential operation topics such as sample introduction and stacking, coated capillaries, and method validation* Recently developed methods, including two-dimensional separations, nonaqueous CE, and HPCE on microchips* All of the basic HPCE applications, with an emphasis on bioanalytical uses* HPCE in the determination of physico-chemical properties of moleculesWith features and capabilities that match--and even surpass--those of conventional electrophoresis and HPLC, high performance capillary electrophoresis (HPCE) is the fastest developing technology for the separation and analysis of chemical compounds. Keeping pace with the rapid changes in this field and the wealth of journal articles on the subject is a difficult and time-consuming challenge for anyone needing a basic and up-to-date grasp of HPCE.This book makes it much easier to find this important information--with comprehensive one-source coverage of all of the essential aspects of HPCE theory, techniques, and applications. Featuring the contributions of well-qualified, highly regarded scientists, it is organized into sections on:* Theory and principles of HPCE techniques* Detection systems* Operation aspects and special methods in HPCE* Uses in chemical analysis* Physico-chemical studiesSpecific topics addressed here that are not treated extensively by other books include two-dimensional separations, CE on microchips, nonaqueous CE, indirect detection, monitoring enzymatic reactions, and more.As interest in HPCE continues to grow, it is clear that this technology has much to offer researchers and others working in disciplines ranging from analytical chemistry and biochemistry to pharmaceutical chemistry and biotechnology. High Performance Capillary Electrophoresis equips scientists and students with the knowledge they need to take immediate advantage of the exciting potential of HPCE.
Chemical analysis ; 146
Keywords: biomedicínské inženýrství; fyzika, biofyzika; elektroforéza kapilární